Determination of CYP2D6*3 and *4 allele frequency among Turkish population - Okat, Zehra; Yaman, Kübra; Çiftçi, Kezban Uçar; Toplayıcı, Selina; Kurt, Elif; Taga, Yavuz (Journal of Surgery and Medicine, 2018)
Aim: CYP2D6 takes part in the family of cytochrome P450 enzymes, which is account for the detoxification of multifarious xenobiotics and various drug commonly used in medicine. CYP2D6 is a polymorphic gene encompassing more than 80 known polymorphism within the coding and promoter regions. The mutant CYP2D6*3 allele revealed with the deletion of A2637 found in exon 5 region. The other common mutant allele is CYP2D6*4 and this allele stem from a splice site defect of G1934A can be classified as the most typical mutations. The present study primarily aims to determine the CYP2D6*3 and *4 frequency defects among Turkish population. Methods: Within the framework of the study, two critical alleles of CYP2D6 wild type allele, and CYP2D6*3 -CYP2D6*4 mutated alleles are genotyped on eighty healthy volunteers, who are unrelated, by the method of polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP). Results: CYP2D6*4 allele frequency, which was identified as the loss of BstNI site, was determined as 13.16% on the examined reference group. Besides, the CYP2D6*4/CYP2D6*4 genotype ratio for the searched reference group was observed in only 2.63%. The heterozygous CYP2D6*3 allele frequency was determined as 1.32% on the examined reference group. Finally, CYP2D6*3/CYP2D6*3 genotype was not encountered in that searched reference group. Conclusion: In the light of those findings, it can be clearly stated that the prevalence of CYP2D6*3 and *4 allelic variants in the Turkish population is the same with the other demographic groups in Turkey.